Coexistence of Slipped Capital Femoral Epiphysis and multiple endocrine neoplasia type 2B (MEN2B) - a case report - Kamila Kędra; Maciej Bielak; Izabela Michalik; Julia Zarańska; Arkadiusz Aab; Karolina Bielak (Kazimierz Wielki University, 2023)
Introduction: MEN 2B syndrome is distinguished by the occurrence of medullary thyroid cancer, pheochromocytoma, mucosal neuromas, marfanoid features, and skeletal anomalies, including kyphoscoliosis, joint laxity, pes cavus, and, in a smaller number of cases, slipped capital femoral epiphysis (SCFE). Case report: We describe a case report of a 15-years-old patient with the diagnosis of the MEN2B syndrome with a rare manifestation of Slipped Capital Femoral Epiphysis (SCFE). A 15-year-old female presented to the orthopedics out-patient department (OPD) with complaints of pain around the right hip and knee and walking with a limp for approximately four months. Additionally, the feeling of enlarged thyroid gland was reported. X-ray confirmed the presence of the SCFE, while thyroid biopsy revealed the presence of  medullary thyroid cancer (MTC). Thus, the diagnosis of MEN2B was made. Conclusion: Slipped capital femoral epiphysis (SCFE) can occasionally be a manifestation of MEN 2B syndrome. It is important for physicians to be aware of this association, as it can contribute to the early detection of a potentially life-threatening condition.